The Exploration of Ethnomathematics Houses Malay ‘Limas Potong’ The Batam Islands of Riau - Fitri Qoriaturrosyidah; Asmaul Husna; Rotua Saulina Pasaribu; Atika Pidianti; Putri Annisa Alwahab (Indonesian Journal of Mathematics Education, 2023)
Ethnomathematics is the study of how a group of individuals in a particular culture understand, communicate, and use cultural ideas and practices that researchers identify as mathematics. To return cultural heritage of traditional house in Batam, Riau Islands, and to further explore the idea of mathematical geometry inherent in the traditional house, so this research aims to explore the ethnomathematics in the Malay Traditional House 'Limas Potong'. This study applied a qualitative approach that was conducted in the Malay Traditional House 'Limas Potong', specifically in the Kampung Melayu neighborhood of Batam City's Nongsa District in the Riau Archipelago. The data used in this research was obtained from these explorations or already-published articles. Observation, interviews, and documentation were used as data collection methods. In this research, data analysis was carried out in two stages: data analysis in the field and data combining. According to the research findings, each decorative and structural part of the Malay Traditional House 'Limas Potong' incorporates mathematical ideas in geometrical shapes and components. Measurement, architectural design, mathematics learning, and application of learning are all related to ethnomathematics in the Malay Traditional House 'Limas Potong'. The construction of the Malay Traditional House 'Limas Potong' can be utilized as a learning resource for students, especially in geometry material, according to some mathematical ideas contained in the structure of the traditional house. Ethnomathematics exploration will inspire teachers to make this a new alternative to developing creativity in students' mathematics learning.